Development of a nanoamorphous exosomal delivery system as an effective biological platform for improved encapsulation of hydrophobic drugs - Tran, Phuong H.L.; Wang, Tao; Yin, Wang; Tran, Thao T.D.; Barua, Hridika T.; Zhang, Yumei; Midge, Snehal B.; Nguyen, Tuong N.G.; Lee, Beom Jin; Duan, Wei (International Journal of Pharmaceutics, 2019)
Despite their great potential, the nano-sized extracellular vesicles are yet to become effective delivery systems for poorly water-soluble drugs. Here, we present a novel platform of exosomes as a drug delivery system by engineering of a poorly water-soluble drug into a poloxamer-based molecular nanostructured dispersion composed of a hydrophilic and a hydrophobic moiety for an enhanced anticancer efficacy. For the first time, aspirin was loaded into exosomes as an anticancer agent via a one-step fabrication combining the nano-matrix formation of the nanostructured dispersion and exosomes loading. Our approach could transform crystalline aspirin to a nanoamorphous form in the nano-matrix structured exosomes, leading to increased drug encapsulation efficiency for exosomes, improved dissolution and strongly enhanced cytotoxicity of aspirin to cancer cells. Interestingly, cytotoxicity of aspirin to both breast and colorectal cancer cells could be strongly enhanced by the nanoamorphous aspirin-loaded exosomes, and this cytotoxic effect was more pronounced to parental cells of the exosomes, reminiscent of homing effect. Hence, this study has pioneered a novel nanoplatform of nanoamorphous exosomal delivery system to transform an anti-inflammatory drug into a potent anti-cancer agent.
Keywords: Antineoplastic Agents; Aspirin; Breast Neoplasms; Cell Line, Tumor; Cell Survival; Colorectal Neoplasms; Drug Delivery Systems; Epoxy Compounds; Exosomes; Humans; Hydrophobic and Hydrophilic Interactions; Poloxamer; Vitamin E; Aspirin; Cancer cells; Cytotoxicity; Exosomes; Nanoamorphous